Respon Tanaman Kedelai (Glycine max (L.) Merril) terhadap Kombinasi Dosis PGPR (Plant Growth Promoting Rhizobacteria) dan Pupuk Phonska - Syafrullah Salman (Paspalum: Jurnal Ilmiah Pertanian, 2019)
This research aims to find out effect of combination dosage of PGPR (Plant Growth Promoting Rhizobacteria) and phonska fertilizer toward the growth and the yield of soybean. This experiment was carried out in the field using a combination randomized block design (RBD) with five repeating.The treatments gave were 100% PGPR fertilizer (8 grams / liter) (A), 100% PGPR fertilizer (8 grams / liter) + 50% phonska fertilizer (0.78 grams) (B), 50% PGPR fertilizer (4 grams / liter) + 100% phonska fertilizer (1.56 gram) (C), 50% PGPR fertilizer (4 gram / liter) + 50% phonska fertilizer (0.78 gram) (D) and 100% phonska fertilizer (1, 56 grams) (E).The results showed that the treatment of 50% PGPR fertilizer (4 grams / liter) + phonska fertilizer 100% (1.56 grams) (C) gave a significant effect on the variable root length and leaf area index (LAI).The treatment of 100% phonska fertilizer (1.56 grams) (E) gave a significant effect on the variable seed weight per plot.